2021
DOI: 10.1155/2021/4632745
|View full text |Cite
|
Sign up to set email alerts
|

MiRNAs in Gestational Diabetes Mellitus: Potential Mechanisms and Clinical Applications

Abstract: Gestational diabetes mellitus (GDM) is a common pregnancy complication which is normally diagnosed in the second trimester of gestation. With an increasing incidence, GDM poses a significant threat to maternal and offspring health. Therefore, we need a deeper understanding of GDM pathophysiology and novel investigation on the diagnosis and treatment for GDM. MicroRNAs (miRNAs), a class of endogenic small noncoding RNAs with a length of approximately 19-24 nucleotides, have been reported to exert their function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 150 publications
(147 reference statements)
0
23
0
Order By: Relevance
“…Although our study could not confirm the clinical impact of universal GDM screening at 24–28 gestational weeks on stillbirth rates ≥24 gestational weeks in the general population, it did show an effect in the high‐risk population. It is speculated that early hyperglycemia, as may be present in women at high risk of GDM, may elicit epigenetic changes and influence fetal and placental programming, which might eventually lead to placental dysfunction 21,41 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our study could not confirm the clinical impact of universal GDM screening at 24–28 gestational weeks on stillbirth rates ≥24 gestational weeks in the general population, it did show an effect in the high‐risk population. It is speculated that early hyperglycemia, as may be present in women at high risk of GDM, may elicit epigenetic changes and influence fetal and placental programming, which might eventually lead to placental dysfunction 21,41 …”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that early hyperglycemia, as may be present in women at high risk of GDM, may elicit epigenetic changes and influence fetal and placental programming, which might eventually lead to placental dysfunction. 21,41 In view of the wide spectrum of medical sequalae associated with GDM, universal GDM screening has been widely accepted as an important public health measure. However, more data are needed to verify the robust effects of GDM screening and total stillbirth reduction in early and late gestational weeks.…”
Section: One Example Of Such Data Is the Midlands And North Of Englandmentioning
confidence: 99%
“…Present trends in GDM investigations are gaining impetus where novel early gestation cellular markers are looked into with serious concern as they may cause serious and irreversible maternal or foetal complications post-childbirth. The miRNAs can be used as potential markers for the early screening of GDM [ 100 ]. A study revealed that the changes in the maternal metabolic processes might be directly linked with variations in the placental miRNA expression.…”
Section: Role Of Microrna In Gdmmentioning
confidence: 99%
“…MicroRNAs are endogenous non-coding RNA molecules with a length of 19-22 nt (7). Many studies have shown that miRNAs are involved in the pathogenesis of GDM (8)(9)(10). miR-199a is differentially expressed specifically in patients with type 1 diabetes, type 2 diabetes and GDM (11,12).…”
Section: Introductionmentioning
confidence: 99%